EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1962)
Abstract This article presents the problems asked in the theory of accounts portion of the November 10, 1961, Uniform Certified Public Accountants Examination. Overall there were 7 problems. Problem #1 asks to assist the chief accountant of a company in the preparation of a balance sheet, given various classifications suggested by the chief accountant for the balance sheet. The second problem asks to define "natural business year" and discuss briefly the reasons for changing the accounting period of a company to a "natural business year." The third problem relates to the recording of the leasehold and the liability on the tenant's books. The fourth problem requires to explain bond indentures and sinking fund. The fifth problem asks to give the journal entries for a companies stock option plan. The sixth problem asks to define "current operating performance. And the final problem belongs to the differences between taxable income and accounting income. The article also presents the solutions for all the given problems.